Prospects for Alternative Energy Development in Uzbekistan - Zhamoliddin o‘gli, Topilov Khasan; Sofia, Alfira; Nur Apandi, Nelly; Khasan, Umarov (The International Journal of Business Review (The Jobs Review), 2024)
Purpose – This study aims to explore the potential and prospects of alternative energy development in Uzbekistan, highlighting the imperative transition to renewable energy sources.Design/methods/approach – This research employs a documentary research method, which involves systematically collecting and analyzing existing documents, records, and data. The methodology integrates archival research and content analysis to provide a comprehensive understanding of Uzbekistan's energy landscape.Findings – The study reveals that Uzbekistan has significant potential for alternative energy development, particularly in solar and wind energy. However, the current utilization of these resources remains minimal. The findings underscore the necessity for policy support, investment, and public awareness to achieve the country's renewable energy goals.Research implications/limitations – The research emphasizes the need for Uzbekistan to invest in renewable energy infrastructure and develop supportive policies to encourage the adoption of alternative energy sources. Limitations of the study include the reliance on secondary data and the focus on Uzbekistan, which may limit the generalizability of the findings.Originality/value – This study contributes to the existing literature by providing a detailed analysis of the prospects and challenges of alternative energy development in Uzbekistan. It offers valuable insights for policymakers, investors, and researchers interested in the transition to renewable energy.